Anaerobic Digestion of Tannery Solid Waste for Biogas Production: The case of Modjo Tannery, Modjo; Ethiopia - Tsegaye, Dejene; Dawit, Mekibib; Gajananda, Khwairakpam (Journal of Technology Innovations in Renewable Energy, 2016)
The present study characterized the physical property, total solids (TS), volatile solids (VS) and Carbon to Nitrogen ratio (C/N ratio) of tannery solid waste (TSW). Five different combinations with or without cow dung (CD) were assessed for their biogas production suitability in triplicate batch digesters (D-1, D-2, D-3, D-4, and D-5) with a total volume of 2.8L. The results showed that TS, VS and C/N ratio of wastes were 56.37%, 76.34% and 29.05%, respectively. The results also suggested that the highest volume of biogas (4,756 ml) with a methane content of 60.37% was produced by the digester containing 75% TSW and 25% CD and the lowest biogas (2,539 ml) with quality of 68.06% was produced by digester containing 100% CD. The average methane contents of different digesters were D-1 (100% TSW) 53.23%, D-2 (75% TSW: 25% CD) 60.37%, D-3 (50% TSW: 50% CD) 58.78%, D-4 (25% TSW: 75% CD) 57.66% and D-5 (100% CD) 67.31%. Total and volatile solid removal efficiency of all digesters was in the range of 42.27-76.34% and 47.16-79.23%. The study concluded that TSW is a good feedstock for biogas production by utilizing agro-industrial based organic solid waste for bioenergy production.